Important role of mitochondria and the effect of mood stabilizers on mitochondrial function - Ľupták, M; Hroudová, J (Physiological research, 2019)
Mitochondria primarily serve as source of cellular energy through the Krebs cycle and beta-oxidation to generate substrates for oxidative phosphorylation. Redox reactions are used to transfer electrons through a gradient to their final acceptor, oxygen, and to pump hydrogen protons into the intermembrane space. Then, ATP synthase uses the electrochemical gradient to generate adenosine triphosphate (ATP). During these processes, reactive oxygen species (ROS) are generated. ROS are highly reactive molecules with important physiological functions in cellular signaling. Mitochondria play a crucial role in intracellular calcium homeostasis and serve as transient calcium stores. High levels of both, ROS and free cytosolic calcium, can damage mitochondrial and cellular structures and trigger apoptosis. Impaired mitochondrial function has been described in many psychiatric diseases, including mood disorders, in terms of lowered mitochondrial membrane potential, suppressed ATP formation, imbalanced Ca(2+) levels and increased ROS levels. In vitro models have indicated that mood stabilizers affect mitochondrial respiratory chain complexes, ROS production, ATP formation, Ca(2+) buffering and the antioxidant system. Most studies support the hypothesis that mitochondrial dysfunction is a primary feature of mood disorders. The precise mechanism of action of mood stabilizers remains unknown, but new mitochondrial targets have been proposed for use as mood stabilizers and mitochondrial biomarkers in the evaluation of therapy effectiveness.
Keywords: energetický metabolismus; Mitochondria; Calcium; Mental Disorders; reaktivní formy kyslíku; vápník; signální transdukce; psychotropní léky; lithium; Psychotropic Drugs; Lithium; duševní poruchy; Signal Transduction; Reactive Oxygen Species; lidé; Energy Metabolism; Humans; Valproic Acid; mitochondrie; kyselina valproová